1982
DOI: 10.1159/000260575
|View full text |Cite
|
Sign up to set email alerts
|

Mirocrystal Arrangement in Human Deciduous Dental Enamel Studied by Electron Paramagnetic Resonance

Abstract: The arrangement of microcrystallites in human deciduous enamel was studied by electron paramagnetic resonance using a stable CO33––radiation centre as a probe. Enamel samples taken from maxillary central deciduous incisors showed a lower degree of crystallite arrangement as compared with samples taken from permanent incisors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
10

Year Published

1984
1984
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 11 publications
1
11
0
10
Order By: Relevance
“…The performance was similar to that found in a recently published in vitro study in deciduous teeth [Attril and Ashley, 2001] as well as in in vitro and in vivo studies in permanent teeth [Lussi et al, 1999[Lussi et al, , 2001Shi et al, 2000]. Permanent and deciduous teeth have different macro-and micromorphological characteristics [Skalerič et al, 1982;Shellis, 1984;Wilson and Beynon, 1989]. These differences could also affect their physical properties and hence the performance of the laser system, e.g.…”
Section: Discussionsupporting
confidence: 85%
“…The performance was similar to that found in a recently published in vitro study in deciduous teeth [Attril and Ashley, 2001] as well as in in vitro and in vivo studies in permanent teeth [Lussi et al, 1999[Lussi et al, , 2001Shi et al, 2000]. Permanent and deciduous teeth have different macro-and micromorphological characteristics [Skalerič et al, 1982;Shellis, 1984;Wilson and Beynon, 1989]. These differences could also affect their physical properties and hence the performance of the laser system, e.g.…”
Section: Discussionsupporting
confidence: 85%
“…In comparison with permanent enamel, primary enamel is less mineralized and more porous. Consequently, the diffusion coefficient seems to be greater in primary than in permanent enamel 27,28 . Moreover, a lower mineralized and thinner surface layer was observed in proximal enamel lesions in primary molars compared with permanent ones 25 …”
Section: Discussionmentioning
confidence: 98%
“…Consequently, the diffusion coefficient seems to be greater in primary than in permanent enamel. 27,28 Moreover, a lower mineralized and thinner surface layer was observed in proximal enamel lesions in primary molars compared with permanent ones. 25 Despite of the better penetration of primary compared with permanent caries lesions after 1-min application and the relatively high percentage penetration found, one should be cautious to recommend this application time for clinical infiltration in young children.…”
Section: Discussionmentioning
confidence: 98%
“…As a consequence, their crowns appear whiter in color. The ordering of the crystallites is probably poorer in milk teeth than in permanent ones (Skaleric et al, 1982). Primary and mature enamels are similar in terms of amino acid composition, except the latter contains more glycine (Wright et al, 1997).…”
Section: Primary Teethmentioning
confidence: 94%
“…Furthermore, as has been widely illustrated in the previous chapters, many carbonate-derived signals look "similar", but may, in fact, have significantly different properties. Skaleric et al (1982) observed that signals of enamel plates from deciduous teeth exhibited a weaker EPR signal anisotropy than signals of plates from permanent teeth. They concluded that the degree of microcrystal arrangement in deciduous teeth is lower.…”
Section: Epr Dosimetry With Primary Teethmentioning
confidence: 98%